2020
DOI: 10.1136/bcr-2020-237616
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and acute kidney injury in severe COVID-19 infection

Abstract: We report the case of a 38-year-old man who presented to the emergency department with fever, myalgia, nausea, vomiting, dry cough, breathlessness and abdominal pain. He was admitted due to hypoxaemia and was diagnosed with SARS-CoV-2 and was subsequently referred to the intensive care unit for intubation and mechanical ventilation. Severe rhabdomyolysis and acute kidney injury developed 4 days later and were suspected after noticing discolouration of the urine and a marked increase in plasma myoglobin levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 10 publications
(16 reference statements)
0
48
1
4
Order By: Relevance
“…of patients with data] 164 (392) [38] 315 (273) [8] 171 (609) [16] 58 (206) [14] 175 (567) [10] Highest, median (IQR) [No. of patients with data] 600 (748) [38] 359 (583) [9] 694 (706) [16] 808 (1374) [14] 485 (885) [11] Creatine…”
Section: Key Pointsmentioning
confidence: 99%
“…of patients with data] 164 (392) [38] 315 (273) [8] 171 (609) [16] 58 (206) [14] 175 (567) [10] Highest, median (IQR) [No. of patients with data] 600 (748) [38] 359 (583) [9] 694 (706) [16] 808 (1374) [14] 485 (885) [11] Creatine…”
Section: Key Pointsmentioning
confidence: 99%
“…Exposure to myotoxic medication could be identified in 18 patients. Myotoxic drugs these patients were taking at the time rhabdomyolysis occurred included azithromycin, hydroxy-chloroquine, placitaxel [5], propofol [6], imastinib, piperacillin and meropenem, hydrochlorothiazide, and acetaminophen (Table). Typical clinical manifestations of rhabdomyolysis (myalgia, dark urine, fever, fatigue, vomiting, diarrhoea) were reported in 20 patients and remained unreported in 10 cases.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 COVID-19 not only causes intrarenal inflammation and increased vascular permeability, but also leads to intravascular volume depletion and cardiomyopathy, thereby precipitating cardio-renal syndrome. 38 Other proposed mechanisms for COVID-associated kidney injury include direct cytopathic effects of SARS-CoV-2 on the podocytes and renal tubules 39 and the consequences of multi-organ dysfunction such as acute tubular necrosis secondary to rhabdomyolysis, 40 renal medullary hypoxia secondary to ARDS and renal compartment syndrome due to high peak airway pressure, and intraabdominal hypertension. 41 Our finding that Black patients with COVID-19 had approximately 2.2 times increased odds of developing inhospital AKI after adjusting for potential confounders has confirmed those of the previous studies in different populations that reported 1.2-2.0 times increased odds of AKI among Black COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%